Deciphering metasomatic events beneath Mindszentkálla (Bakony-Balaton Highland Volcanic Field, western Pannonian Basin) revealed by single-lithology and composite upper mantle xenoliths - Patkó, Levente; Kovács, Zoltán; Liptai, Nóra; Aradi, László E.; Berkesi, Márta; Ciazela, Jakub; Hidas, Károly; Garrido, Carlos J.; Kovács, István J.; Szabó, Csaba (Frontiers in Earth Science, 2022)
Single-lithology and composite xenoliths from Mindszentkálla (Bakony-Balaton Highland Volcanic Field) in the Carpathian-Pannonian region record geochemical evolution of the subcontinental lithospheric mantle. The dominant single-lithology xenoliths are orthopyroxene-rich (22 vol.% on average) harzburgites. Three composite xenoliths contain either two or more domains including dunite, olivine-orthopyroxenite, orthopyroxenite, apatite-bearing websterite and amphibole-phlogopite-bearing vein. The presence of different lithologies is a result of at least two metasomatic events that affected the lithospheric mantle. The first event resulted in orthopyroxene enrichment thus formed harzburgitic mantle volumes (Group I xenoliths). Major- and trace element distributions of the bulk harzburgites differ from the geochemical trends expected in residues of mantle melting. In contrast, petrographic and geochemical attributes suggest that the harzburgite was formed by silica-rich melt - peridotitic wall rock interactions in a supra-subduction zone. Within the Group I xenoliths, two subgroups were identified based on the presence or lack of enrichment in U, Pb and Sr. Since these elements are fluid mobile, their enrichment in certain Group I xenoliths indicate reaction with a subduction-related fluid, subsequent to the harzburgite formation. The effect of a second event overprints the features of the Group I xenoliths and is evidenced in all domains of two composite xenoliths (Group II xenoliths). The general geochemical character involves enrichment of basaltic major and minor elements (Fe, Mn, Ti, Ca) in the rock-forming minerals and convex-upward rare earth element (REE) patterns in clinopyroxenes. We suggest that the different domains represent reaction products with variably evolved basaltic melts of a single magmatic event. The tectonic background to the formation of Group I xenoliths is likely linked to the subduction of oceanic crust during the Mesozoic–Paleogene. This happened far from the current position of Mindszentkálla, to where the lithosphere, including the metasomatized mantle volume, was transferred via plate extrusion. The Group II xenoliths appear to bear the geochemical signature of a younger (Neogene) basaltic magmatic event, likely the same that produced the host basalt transporting the xenoliths to the surface.